Psychosocial Factors at Work in the Asia Pacific From Theory to Practice - Shimazu, Akihito; Bin Nordin, Rusli; Dollard, Maureen; Oakman, Jodi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents research and practice from the Asia Pacific to address the gap in the global stock of knowledge of psychosocial factors at work. It explores the region and focuses on practices that promote healthy workplaces and workers by presenting research from around the globe on issues such as telework, small and medium-sized enterprises, disaster areas, suicide prevention, and workplace client violence. It discusses multidisciplinary efforts with a practical approach to addressing worker occupational health and provides examples and research. It also explores psychosocial risk and prevention as well as the significant cultural variations and practices in the diverse range of countries covered. .
Part I: Policy and Practice Framework in the Asia Pacific and Beyond -- Chapter 1. The Context of Psychosocial Factors at Work in the Asia Pacific: Update. Jodi Oakman, Maureen F. Dollard, Akihito Shimazu, Rusli Bin Nordin -- Chapter 2. Is Psychosocial Risk Prevention Possible? Deconstructing Common Presumptions. Stavroula Leka -- Chapter 3. Macro Level Policy and Practice Relating to Psychosocial Factors at Work in the Asia Pacific. Tessa S Bailey, Yawen Cheng, Awang Idris, Sara Arphorn, Maureen Dollard -- Chapter 4. Guidelines for Primary Prevention for Mental Health at Work in Japan. Akizumi Tsutsumi, Toru Yoshikawa, Akihito Shimazu. Chapter 5. Guidelines on Preventing Work-related Stress in Korea -- Jungsun Park -- Part II. Psychosocial Factors at Work in the Asia Pacific -- Chapter 6. Psychosocial Safety Climate: What we Learnt from Qualitative Explanation? Siti Balqis, Awang Idris, Maureen F. Dollard -- Chapter 7. Designing Work that Works: Future Directions for Job Design Research and Practice. Sharon Parker -- Chapter 8. Prevalence, Distribution and Trends of Workplace Violence and its Associated Health Problems: Results from National Surveys of Taiwan. Yawen Cheng -- Chapter 9. Psychosocial Hazards and Musculoskeletal Disorders: Does the Country you Work in Make a Difference to the Role of Workplace Factors? Jodi Oakman, Ismail Maakip, Tessa Keegel -- Chapter 10. Psychosocial Safety Climate from Two Different Cultural Perspectives in the Asia Pacific: Iranian and Australian Healthcare Contexts. Ali Afsharian, Amy Zadow, Maureen Dollard -- Part III. Practical approach Towards Healthy Workplaces and Workers -- Chapter 11. An International Evaluation of Workplace Psychosocial Management Approaches. Alice Fattori, Tessa Bailey, Maureen Dollard, Evelyn Kortum -- Chapter 12. Development of the New Brief Job Stress Questionnaire. Akiomi Inoue, Norito Kawakami, Teruichi Shimomitsu, Akizumi Tsutsumi, Takashi Haratani, Toru Yoshikawa, Akihito Shimazu, Yuko Odagiri -- Chapter 13. Occupational Stress and Coping Strategies among Malaysian Employees. Cindy Biding Ahin, Rusli Bin Nordin -- Chapter 14. Effects of an Internet-Based Cognitive Behavioral Therapy Intervention on Improving Work Engagement and Other Work-Related Outcomes: An Analysis of Secondary Outcomes of a Randomized Controlled Trial. Kotaro Imamura, Norito Kawakami, Toshi A. Furukawa, Yutaka Matsuyama, Akihito Shimazu, Rino Umanodan, Sonoko Kawakami, Kiyoto Kasai -- Chapter 15. Organizational Support for Mental Health, Stigmatization of Employees with Depression and Performance Appraisal: A Management Simulation Study. Angela Martin. Part IV. Practical Approach in Specific Conditions -- Chapter 16. Efforts to Improve Mental Health Activities in Japanese Micro- and Small-Scale Enterprises: Development of Support Tools for Employers. Jiro Moriguchi, Sonoko Sakuragi, Masayuki Ikeda -- Chapter 17. How to Manage the Health Issues of Workers Engaged in Operations Related to the Accident at the Fukushima Daiichi Nuclear Power Plant and Lessons Learned from the Experiences. Koji Mori -- Chapter 18. Association Between Workplace Clients$1 (BViolence and Burnout in Korean Service Workers. Sei-Jin Chang -- Chapter 19. The Effect of a Nation-Specific Stressor on Wellbeing: Guanxi in Chinese Workplace. Qiao Hu, Wilmar B. Schaufeli, Toon W. Taris -- Chapter 20. Beneath the Surface: An Exploration of Isolation And Work Stress in Mining Work. Wes McTernan -- Part V. Conclusion -- Chapter 21. Psychosocial Factors at Work in the Asia Pacific: Where to Go? Akihito Shimazu, Jodi Oakman, Maureen F. Dollard, Rusli Bin Nordin.s
Keywords: Applied psychology; Quality of life -- Research; Personnel management; Psychology, Clinical; Industrial sociology; Industrial and Organizational Psychology; Quality of Life Research; Human Resource Management; Health Psychology; Community and Environmental Psychology; Sociology of Work